2019
DOI: 10.1097/cm9.0000000000000232
|View full text |Cite
|
Sign up to set email alerts
|

DL-3-n-butylphthalide protects the blood-brain barrier against ischemia/hypoxia injury via upregulation of tight junction proteins

Abstract: Background: The increased permeability of the blood-brain barrier (BBB) induced by ischemia/hypoxia is generally correlated with alteration of tight junctions (TJs). DL-3-n-butylphthalide (NBP) has been shown to exert neuroprotective effects after ischemic injury. However, few studies have assessed the correlation between NBP and TJs. This study aimed to investigate the potential effect of NBP on the TJ proteins claudin-5, zonula occludens-1 (ZO-1), and occludin during brain ischemia. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 24 publications
4
23
0
Order By: Relevance
“…Disruption of BBB integrity is one of the key factors in the pathological damage of white matter hyperintensities burden . This result suggests that dl-NBP may increase the integrity of white matter through increasing the integrity of the BBB via upregulating the expression of tight junction proteins, which is consist with a previous study showing that NBP reduced ischemia-induced BBB damage via upregulation of tight junction proteins (Ye et al, 2019).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Disruption of BBB integrity is one of the key factors in the pathological damage of white matter hyperintensities burden . This result suggests that dl-NBP may increase the integrity of white matter through increasing the integrity of the BBB via upregulating the expression of tight junction proteins, which is consist with a previous study showing that NBP reduced ischemia-induced BBB damage via upregulation of tight junction proteins (Ye et al, 2019).…”
Section: Discussionsupporting
confidence: 89%
“…BBB integrity is important for functional recovery after ischemic stroke and dl-NBP has been demonstrated to alleviate ischemia-induced blood-brain barrier (BBB) damage via promoting the expression of tight junction proteins (Ye et al, 2019). Here, we checked the effect of dl-NBP on the expression of the tight junction protein occludin.…”
Section: Dl-nbp Treatment Enhanced the Number Of Reca-1 Positive Vessmentioning
confidence: 99%
“…es in the integrity of the BBB [9]. Tight junction proteins have a role in neuronal injury, and the expression of ZO-1 and occluding proteins protects against neuronal injury [23]. We found that treatment with melodinhenine B normalized the altered expression of ZO-1 and occluding proteins in the cerebral tissues of I/R-induced neuronal injury rats.…”
Section: Discussionmentioning
confidence: 71%
“…Imaging research into stroke patients showed that BBB dysfunction can be thought as a striking attribute of the periischemic brain (Bang et al, 2007). The TJs, which are composed of cytoplasmic proteins, transmembrane proteins, and junction adhesion molecules between capillary endothelial cells, are very important in maintaining BBB integrity (Ye et al, 2019). Among them, ZO-1, claudin-5, and occludin are the most important proteins in TJs.…”
Section: Discussionmentioning
confidence: 99%